EXAMINING HOW ENGLISH TEACHERS' REQUESTS ARE USED IN INTERACTIONS WITH STUDENTS IN INDONESIAN CLASSROOMS - Hasanah, Nurul; Mahmud, Murni (JTechLP: Journal of Technology in Language Pedagogy, 2023)
This study aims to investigate the request expressions that English teachers use during EFL classroom interactions. It is essential to use requests in the classroom to foster productive student interaction. Teachers can encourage politeness and discourage unpleasant behavior in the classroom by using requests. This study is qualitative in nature. It was held at a single senior high school in Pangkep, Indonesia's South Sulawesi. Four English teachers are the research subjects. The teaching methods of the four teachers were videotaped, written down, and examined in order to gather data. Four lengthy snippets of the teaching process were recorded, then examined to investigate the request expressions that instructors employ out of courtesy. The information gathered was examined using the politeness procedures proposed by Brown and Levinson (1987). The study's findings demonstrate that educators used bald, negative, and positive on-record techniques in accordance with Brown and Levinson's theory (1987). Teachers utilize terms like "please," "tolong," "-ki," "dulu," "coba," "ya," "can," "may," "maybe," "a little bit," and "have to" while making requests. In addition, certain direct request expressions (jangan, don't) and terms of address (Nak, Mam, student's name) were employed. Teachers in the class used those expressions as a kind of civility. These results demonstrate the value of civility in classroom interactions. Teachers and students utilize the study's findings as a guide to promote positive interactions in the classroom.